Main Plant Growth of Teak (Tectona grandis Linn F.) in Small Scale Private in Conggeang District, Sumedang Regency. - Asep Hendra Supriatna; Nurheni Wijayanto (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
The need for teak wood processing in Indonesia is still high both for domestic demand and export wood demand. But the shortage of teak wood demand can give opportunities for people to cultivate teak on their privately land. The purpose of this research is to examine the main plant growth of teak (Tectona grandis Linn F.) in small scale private forest and compare it with teak’s growth from monoculture forest at Perum Perhutani KPH Sumedang in same ages. The main data of plant dimensional were taken with census method from teak plants in each of the selected land such as height, canopy diameter and canopy projection. In this research, soil parameter observed consist of physical and chemical content of soil samples from each selected land then analyzed in laboratory. Crown closure data taken by using a spiracle densiometer. The history of land management known by interview with farmers in each selected land. Those data were analyzed descriptively. The results showed that the observed forest have 3 (three) different age classes of teak plantation. They are teak plant with class age of 3 years, 6 years, and 12 years whom the growth of teak are different in those parameter such as diameter, height, crown closure and basal area. Growth of teak plantation in the village of Babakan Asem is a plant with the best teak growth among the other villages. Their growth maybe influenced by several factors, that is the condition of the site or soil condition factors and cultivation activities. The result of crown closure show that the majority of sunlight blocked by the crop canopy of teak, so less than 40% of sunlight can reach the soil surface. That condition maybe affected by size crop of teak and the distance between teak plantation it self. The result of soil analysis indicated that physical and chemical soil content in Conggeang District are impact on teak growth which bulk density, water storage, KTK, pH, and other chemical substance are related to teak diameter’s growth. Growth of teak plantation between small scale private forest and Perum Perhutani were significantly different in class ages of 3 and 12 years and didn’t different at class ages of 6 years in diameter. The difference in teak growth between small scale private forest and Perum Perhutani are caused by a factor of using teak seed and the forest management.